Strip – metoda, ki fantom omogoča uspešnejšo interpretacijo mladinskega literarnega besedila - Kerneža, Maja; Kordigel Aberšek, Metka (Revija za elementarno izobraževanje, 2014)
Comics – a Method that Allows Boys Deeper Experience of Children’s Literature. In the acquisition of reading skills girls are more successful than boys. As a method of interpretation comics could allow boys a deeper perception, understanding and evaluation of youth literary texts, and help them to express their literary perception experience. The main research method is case study with a number of linguistic motivations used. After getting acquainted with the comics, the students applied new knowledge to detect textual information embedded in stage directions, and expanded their literary worlds by converting texts into comic form. The research is based on qualitative research methods of literary didactic research. Boys’ deficits were successfully compensated – in some cases they were even more successful than girls, and the mehod of work also suited girls.
Keywords: reading literacy; comics; receptive competence; gender differences; boys